Developing of STEM Integrated Web-Students’ Worksheet with Scaffolding to Improve Conceptual Understanding for Physics Education Students - Menza Hendri; Dian Pertiwi Rasmi; Jeliana Veronika Sirait; Asnidar Siahaan; Lastama Sinaga (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
The low conceptual understanding of physics education students, often caused by conventional teaching materials and a lack of self-study guidance, indicates the need for innovation. This research aims to develop a web-based student worksheet (web-LKPD) integrated with the STEM approach and supplemented with scaffolding. The developed web-LKPD is designed to improve the conceptual understanding of physics education students. The method used is research & development with the ADDIE development model (analysis, design, development, implementation, and evaluation). The subjects of this study were physics education students at the Faculty of Teacher Training and Education, Jambi University. The instruments included questionnaires, interviews, conceptual understanding tests (pretest and posttest), and student response questionnaires. The data were analyzed using quantitative and qualitative descriptive techniques. The results showed that the developed web-LKPD was highly suitable for use, evidenced by the average feasibility percentage from media experts of 93% and material experts of 83.2% (very good). The product also received a positive response from students (89.7%, very good). Paired t-test analysis concluded that there was a significant difference between the pretest and posttest results, indicating that the web-LKPD has a significant impact on improving students' conceptual understanding.